MODEL APLIKASI SISTEM PELAYANAN ADMINISTRASI PENDUDUK BERBASIS WEB PADA KANTOR KELURAHAN - soegiarto; Eka Candra Kirana (UNIVERSITAS STEKOM, 2018)
Abstract The process of residential administration services to the community at the head of the village office is generally still done manually. Applicants should come to the head of the village office to find out the service procedures, queue up in service, so that the service process takes time that often exceeds the maximum set time standard. Uncertainty over the completion of delayed services on subsequent days is also frequent due to lack of mechanisms to monitor progress of service completion. Service officers also can not flexibly work in providing services because they have to be in place and time that has been set. This research develops a model of integrated Web-based public service system application at kelurahan office, using R & D research and development method, which is implementing some part of development method of SDLC (System Development Life Cycle) Software. The result of user test (user acceptance) shows that the application of the built system can help facilitate the community and management in head of the village office, and accelerate the process of population administration services to the community.